1995
DOI: 10.1128/aac.39.2.346
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of cphA or related carbapenemase-encoding genes and production of carbapenemase activity in members of the genus Aeromonas

Abstract: The prevalence of the cphA gene or related carbapenemase-encoding genes was investigated in 114 Aeromonas strains belonging to the six species of major clinical interest. A species-related distribution of cphA-related sequences was observed. Similar sequences were found in A. hydrophila, A. veronii bv. sobria, A. veronii bv. veronii, and A. jandaei, but not in A. caviae, A. trota, or A. schubertii. However, a single A. caviae strain (of 62 tested) was found carrying cphA-related sequences, suggesting the possi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
27
0
3

Year Published

2002
2002
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(38 citation statements)
references
References 21 publications
7
27
0
3
Order By: Relevance
“…cphA-related genes were noted in A. veronii and A. hydrophila, but not in A. caviae. Such results were concordant CphA in bacteraemic Aeromonas isolates with those in previous studies (Balsalobre et al, 2009;Rossolini et al, 1995). However, it is a novel finding that the cphA-related genes were present in all A. aquariorum isolates.…”
Section: Discussionsupporting
confidence: 76%
See 3 more Smart Citations
“…cphA-related genes were noted in A. veronii and A. hydrophila, but not in A. caviae. Such results were concordant CphA in bacteraemic Aeromonas isolates with those in previous studies (Balsalobre et al, 2009;Rossolini et al, 1995). However, it is a novel finding that the cphA-related genes were present in all A. aquariorum isolates.…”
Section: Discussionsupporting
confidence: 76%
“…The only exception, A. aquariorum A2-155, was susceptible to imipenem even when tested with a large inoculum. Rossolini et al (1995) found that 20 % of cphA hybridized-positive A. hydrophila and A. veronii bv. sobria isolates were unable to express MBL activity, and they proposed that genetic modification had led to silencing of cphA in these species.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Electroporation of E. coli DH5␣ was performed with a Gene-Pulser apparatus (Bio-Rad Laboratories, Richmond, Calif.), according to the instructions of the manufacturer. Southern hybridization was carried out directly on the dried gels, as described previously (34), with DNA probes labeled with 32 P by the random-priming technique. The bla CTX-M probe was made by use of a 1:1 mixture of amplicons generated with primers CTX-MU1 and CTX-MU2 from bla CTX-M-2 and bla CTX-M-15 , respectively.…”
Section: Methodsmentioning
confidence: 99%